Anton von Webern - Hayes, Malcolm (London Phaidon Press, 1995)
Anton von Webern's reputation as the originator of avant-garde music has conspired against a true recognition of one of the twentieth-century's greatest composer's. He was a pupil of Schoenberg and, like his teacher, he came to use the twelve-note method, but combined this with his love of chamber music to create a sound that was entirely his own. Single-minded and a perfectionist, he created an ouevre of extreme concentration. In this unique biography, Malcolm Hayes sets Webern's radical technical advances against the Romantic inheritance of nineteenth-century Austro-Germany, tracing the development of a man and his music. For those seeking a deeper enjoyment or understanding of Webern's work, this fluent introduction is essential reading.